Physical and mechanical properties of juvenile mahogany / Mohd Aminuddin Che Harun … [et al.] - Che Harun, Mohd Aminuddin Che Harun; Jamaludin, Mohd Azli; Marzuki, Khairunna'im; Raja Othman, Raja Syamsuzzaman (2007)
Juvenile mahogany wood (Swietenia Macrophylla) is one of raw materials which is not much information about it. So, the focus of this study is to examine the physical and mechanical properties for two portion of wood. The portion are heartwood, part near the pith and sapwood, part near bark which being chose from Jengka 8, which is one of the project by FRIM. This study test was done accordance with 'British Standard'. (BS 373:1957: Testing Small Clear Specimen of Timber). For heartwood, MOR and the density differed significantly (p<O.05), but low for MOE, moisture content, thickness swelling and water absorption. It is hoped that the value derived from this study can beneficial and being use as a guide.